Peningkatan Solidaritas Dan Kesejahteraan Bersama Dalam Sila Ke-5 Pancasila - Mima Defliyanti Saragih; Yakobus Ndona (International Forum of Researchers and Lecturers, 2024)
Increasing solidarity and shared prosperity in the 5th Principle of Pancasila refers to efforts to strengthen relations of togetherness and improve conditions of prosperity for the entire community. Solidarity emphasizes the importance of cooperation and mutual cooperation between individuals in society, while welfare includes aspects of social justice and equal opportunity and access to resources. This article aims to analyze creating a society that is united, mutually supportive and socially just. The method used in this research is a literature study by collecting data from various trusted sources. The results of this discussion show that by strengthening solidarity, society will be more united in togetherness and support each other, while prosperity will create conditions where every individual feels safe, comfortable and has equal opportunities to develop.